REARING OF RIVER CATFISH (Mystus nemurus C.V) ON A RECIRCULATION SYSTEM USING SYSTEM FILTERS - Nila Chairu Inda Nurdina; Mulyadi '; Rusliadi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted from April to May 2013, for 45 days in Breeding Laboratory Unit of Fisheries Faculty and Marine Sciences, University of Riau Pekanbaru. The aims research was to improve water quality through a recirculation system by using different filters to rear of river catfish (Mystus nemurus). The Method used was experiment with 4 treatments and 3 replications. The treatments were P0 = control, P1 = roofed substrate, gravel, and sand, P2 = zeolites substrate, P3 = sponge substrate. The best result was treatment P2 with absolute growth weights (4,01 g), absolute growth length (5,18 cm), daily growth rate (1,96 %) and survival rate 91,11%. Water quality parameters were recorded during in the research such as ammonia (NH3) 0,02-0,07 mg/l, nitrite (NO2) 2,43-0,02 mg/l, nitrate (NO3) 4,32-0,04 mg/l, temperature 29-310 C, pH 5-6, dissolved oxygen (DO) 3,90-4,90 mg/l and (CO2) 7,99-11,98 mg/l respectively.Key words : River catfish (Mystus nemurus), recirculation, filters